Effect of the Bocartes Model on Cognitive Knowledge and Learning the Long Jump Event for Students - Hussein, Amena Kareem (Indonesian Journal of Sport Management, 2024)
The current work aims to identify the effect of the Bocartes model on cognitive knowledge. As well as to identify the effect of the Bocartes model on learning the long jump event. The researcher used a two-group (experimental and control) experimental design. The researcher identified her research population as first-year students at the College of Physical Education and Sports Sciences, Kirkuk University for the academic year (2023-2024), numbering (213) students. As the long jump event is part of the vocabulary of a curricular subject at this stage. The research population was divided into four groups. The results showed that the directed-Bocartes model had a positive impact on the cognitive knowledge process. The experimental group outperformed the control group in cognitive knowledge experience. The directed-Bocartes model had a positive impact on learning the long jump. This is through significant differences in favor of the post-test for both the experimental and control groups. One of the most important recommendations is to adopt the directed-Bocartes method when teaching sports events in the arena and field, including the event of the long jump. Also, to adopt cognitive knowledge as a basis in the educational curricula and as required to learn different skills.